Extruded hot compacted alumix 431 powder - mechanical properties and microstructure - Szczepanik Stefan; Nikiel Piotr (Science of Sintering, 2023)
Extrusion at 450°C of hot compacted premixed aluminium alloy powder 7075 resulted in full density and banded microstructure with the average transverse grain size of 13.6 μm after T6 heat treatment. It increased mechanical properties to yield and tensile stresses of 457 and 492 MPa, respectively and elongation 6.4 %. These meet the requirements of the ASTM standard ASM for 7075T6 conventionally manufactured alloy of similar chemical composition. The respective microstructures were compared and also to that of previously reported extruded fully dense 7075 Al which was not heat treated, and so possessed lower mechanical properties, yield and tensile stresses 254 and 402 MPa, respectively and elongation 10.4 %.